Creating positive out-group attitudes through intergroup couple friendships and implications for compassionate love. (August 2014) - Welker, Keith M.; Slatcher, Richard B.; Baker, Lynzey; Aron, Arthur
Building personal relationships with out-group members is an important catalyst of positive intergroup attitudes. In a 2 × 2 experimental design, Caucasian and African American individuals and couples were randomly assigned to interact in either cross-race or same-race individual dyads and couple pairs. Participants completed pretest measures of race attitudes and engaged in a high self-disclosure closeness-induction task with an in-group or out-group race member in pairs of couples or individuals and completed measures of self-disclosure and intergroup attitudes. These results suggest that intergroup contact in the presence of romantic partners may be particularly effective for improving intergroup attitudes. We explore the implications of these results for developing compassionate love toward out-groups.